2022
DOI: 10.3390/ijms232012317
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin Gating: A New Twist to Unravel Permeation through Water Channels

Abstract: Aquaporins (AQPs) are small transmembrane tetrameric proteins that facilitate water, solute and gas exchange. Their presence has been extensively reported in the biological membranes of almost all living organisms. Although their discovery is much more recent than ion transport systems, different biophysical approaches have contributed to confirm that permeation through each monomer is consistent with closed and open states, introducing the term gating mechanism into the field. The study of AQPs in their nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 199 publications
(247 reference statements)
0
8
0
Order By: Relevance
“…Loop A, and its homologous sequences in non-PIP orthodox AQPs, typically engage in direct hydrogen bonding contacts and/or disulfide bridges to help with monomer association and tetramer assembly 27 . AQP proteins are ubiquitously found as tetramers, but each monomer constitutes a functionally independent pore 28 . We used SoPIP2;1 monomers to complete this study due to the computational efficiency and literature-based justification (see “Methods—System assembly”).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Loop A, and its homologous sequences in non-PIP orthodox AQPs, typically engage in direct hydrogen bonding contacts and/or disulfide bridges to help with monomer association and tetramer assembly 27 . AQP proteins are ubiquitously found as tetramers, but each monomer constitutes a functionally independent pore 28 . We used SoPIP2;1 monomers to complete this study due to the computational efficiency and literature-based justification (see “Methods—System assembly”).…”
Section: Resultsmentioning
confidence: 99%
“…Lateral exchange of annular shell lipids with the bulk has therefore been suggested as a regulatory mechanism for AQP function 39 . Conserved channel residue rearrangements have also been posited as a regulatory means to affect AQP water transport 28 , 39 . Perhaps lipid binding itself could be the fundamental driver of either proposed regulatory mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid changes in cell membrane permeability are thought to be associated with the opening/closure of AQPs as a result of changes in their conformation. This mechanism, known as AQP gating, can be realized by chemical, mechanical, and even electrical stimuli [45,46]. Vandeleur et al's work on shoot-to-root signaling showed that leaf cutting in soybean and maize plants caused rapid, within a few minutes, changes in turgor pressure and membrane permeability in the root cells [47].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liang Fang and co-authors showed that changes in the stomatal conductance, root and leaf hydraulic conductance, and AQP gene expression in tomato plant roots under increasing atmospheric CO2 concentration were accompanied by changes in the xylem sap pH [61]. The change in pH can both act as an activator of hydrogen peroxide synthesis and directly affect the activity of AQPs via phosphorylation [45]. Thus, the change in xylem sap pH under water stress can be an additional regulatory factor.…”
Section: Discussionmentioning
confidence: 99%